An investigation into the cause of the inner dark areas and outer lighter areas (ghosting) seen in dynamically-created two-dimensional bare footprints. Issue 4 (July 2017) - OBE, Wesley Vernon; Simmonite, Neil; Reel, Sarah; Reidy, Selina
Abstract: Dynamic bare footprints differ from static bare footprints through the presence of additional, lighter markings around the rear of the heel print and apices of the toe print areas. These images can appropriately be described as inner dark and outer ghosting features. To date, the functional cause of both features has not been understood. To gain such an understanding could potentially allow the further development and use of these features in forensic identification. The aim of this project was to investigate the causes of the inner dark and outer ghosting features seen in dynamic bare footprints through an observational, practice-based action research approach within a gait laboratory. Volunteer male participants provided bare footprints on inkless paper taped to a Kistler force plate with video cameras situated either side. Ground reaction force data were collected as the footprints were formed and the event recorded using video cameras to allow these data to be correlated later. The findings suggest that the ghosting at the heel is the result of splaying of the fibro fatty pad, while that at the toes is the result of the distal ends of the toes coming into contact with the ground as the heel is lifted. Footprint, ground reaction force and video data comparisons showed that the inner dark area of the heel print corresponded with the main body of the heel contacting the ground. Outer ghosting corresponded with a backward splaying of the fat pad and the heel strike transient spike in vertical ground reaction force during increased loading. The inner dark area of the toes corresponded with a longer period of toe contact with the ground. Outer ghosting corresponded with the decreasing vertical ground reaction force and shorter contact time as the toes were leaving the ground towards the end of the contact phase of gait. Although the sample size was limited, these are new appreciations which could facilitate the use of the inner dark features in identification to provide additional points for comparison in cases involving dynamic bare footprints. Further work is now indicated to study these features in different populations and under varying conditions. Highlights: The causes of the inner dark and ghosting features of dynamic bare footprints shown. Develops the use of bare footprints in identification. Suggestions for further work are indicated.